Strategi Kebijakan Pemerintah Provinsi DKI Jakarta dalam Menanggulangi Tantangan Transportasi Perkotaan - Setiawan, Bunga Fayza; Rizal, Vanka Karisa Sabrina; Mahendra, Wahyu (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The Jakarta Provincial Government faces significant challenges in managing urban transportation amidst the rapid growth of the city. Traffic congestion, air pollution, and the increasing volume of vehicles pose major issues. In addressing these challenges, the Jakarta Provincial Government has implemented various strategic policies. The development of public transportation, restrictions on private vehicles, and the empowerment of buffer zones are the primary focuses. This research aims to determine the Policy Strategies of the Jakarta Provincial Government in addressing urban transportation challenges. The study employs a qualitative approach with a literature review as its data collection technique. The results indicate that the Jakarta Provincial Government has implemented a comprehensive policy strategy to tackle urban transportation challenges. This includes the development of public transportation, restrictions on private vehicles, infrastructure investment, technology utilization, and the empowerment of buffer zones. The government has also demonstrated a commitment to creating an efficient, sustainable, and responsive transportation system. Keywords: Government Policy Strategy, Urban Transportation,Government Policy Strategies, Urban Transportation, Transportation Challenges, Public Policy